Informal reasoning fallacy and critical thinking disposition among Malaysian undergraduates - Ramasamy, Shamala (2014)
In this information age, the amount of complex information available due to technological advancement would require undergraduates to be extremely competent in processing information systematically. Critical thinking ability of undergraduates has been the focal point among educators, employers and the public at large. Poor critical thinking ability would hinder undergraduates in coping with everyday life situations which may lead them to become gullible citizens. Encouraging critical thinking among undergraduates requires scrutiny in its theory. A dearth of relevant literature on the current issues of critical thinking has been delved into. One of the dimensions of critical thinking is informal fallacy. Informal fallacies are erroneous thinking. Informal fallacy has the ability to distract us in thinking critically. Fallacies are termed as inferences because they tend to appear reasonable and their unreliability is not apparent on the surface. They have psychological dimensions which are in the form of illusions and deceptions that humans are prone to and have great persuasive power, hence the widespread use in everyday discourse. Informal reasoning fallacy is the crux of this research due to the role of evidence and argumentation in making a conclusion, decision or solving problems. Empirical research affirms that critical thinking involves cognitive skills and the willingness to think critically. Critical thinking dispositions and informal reasoning fallacy are integral essence in facilitating students to have high ability in thinking critically. The purpose of the study was to examine the performance of informal reasoning fallacy ability and critical thinking disposition among Malaysian undergraduates. The second purpose is to add on to the deficit literature review by ascertaining the relationship between informal reasoning fallacy and critical thinking disposition among Malaysian undergraduates. The final purpose is to determine the influence of undergraduates’ background variables to critical thinking, such as gender, discipline of study, programme of study, year of study, age, academic achievements, weekly reading hours and parents’ socio economic status, would be of great concern to the educators and policy-makers. Data collection was gathered from 630 undergraduates, testing them on informal reasoning fallacy and critical thinking disposition. Findings reported that a moderate performance was shown by the undergraduates in informal reasoning fallacy and critical thinking disposition. A significant relationship between informal reasoning fallacy and critical thinking disposition was revealed, indicating that fallacy detection and critical thinking disposition work conjointly. Demographic variables were not significant contributors to critical thinking, hence Malaysian undergraduates are not disadvantaged by their background in their ability to detect fallacies and to be disposed to think critically. This discovery may shed light on educators to embark on critical thinking cultivation without the fear of how students’ background may impact the process of critical thinking in classrooms.